Whole genome sequencing of M. tuberculosis for detection of drug resistance: a systematic review - Papaventsis,D; Casali,N; Kontsevaya,I; Drobniewski,F; Cirillo,DM; Nikolayevskyy,V (Clinical Microbiology and Infection, 2016)
OBJECTIVES: We conducted a systematic review to determine the diagnostic accuracy of Whole Genome Sequencing (WGS) of M. tuberculosis for the detection of resistance to first and second line anti-tuberculosis (TB) drugs. METHODS: The study was conducted according to the criteria of the Preferred Reporting Items for Systematic Reviews group. A total of 20 publications were included. The sensitivity, specificity, PPV and NPV of WGS using phenotypic Drug Susceptibility Testing (DST) methods as a gold standard were determined. RESULTS: Anti-TB agents tested included all first line drugs, a variety of reserve drugs, as well as new drugs. Polymorphisms in a total of 53 genes were tested for associations with drug resistance. Pooled sensitivity and specificity values for detection of resistance to selected first line drugs were 0.98 (95% CI, 0.93 to 0.98) and 0.98 (95% CI, 0.98 to 1.00) for rifampicin and 0.97 (95% CI, 0.94 to 0.99) and 0.93 (95% CI 0.91 to 0.96) for isoniazid, respectively. Due to high heterogeneity in studies' design, lack of data, knowledge of resistance mechanisms and clarity on exclusion of phylogenetic markers, there was a significant variation in analytical performance of WGS for the remaining first-line, reserved drugs and new drugs. CONCLUSIONS: WGS could be considered a promising alternative to existing phenotypic and molecular DST methods for rifampicin and isoniazid pending standardization of analytical pipelines. To ensure clinical relevance of WGS for detection of M. tuberculosis complex drug resistance, future studies should include information on clinical outcomes.